EXAMINATION OF SPORTS HABITS IN DISADVANTAGED SETTLEMENTS - Lukács, Ákos; Lenténé Puskás, Andrea (Stadium - Hungarian Journal of Sport Sciences, 2022)
The study aims to explore sporting habits and sporting opportunities among the young and middle-aged adult population living in disadvantaged settlements.Method: As secondary research, we reviewed the literature related to the topic, studied the legislation on the classification of settlements, and analyzed the CSO data. As primary research, we conducted an online questionnaire survey among adults aged 18 to 60 living in 6 disadvantaged settlements. The questionnaire was shared in specific groups on a community site accessible to 870 people. One hundred sixty-one people completed the questionnaire.Results: Our study found that most regular athletes perform intellectual work; however, they typically perform sports activities only once a week. Most traditional athletes have a high school diploma, and the proportion of university graduates is relatively low. The research results also revealed that most people living in disadvantaged settlements prefer individual sports over team sports; however, this shows a significant difference in gender breakdown between men and women. The proportion of women who like individual sports is significantly higher, while this is reversed in the case of team sports.